Sifat Anatomi dan Sifat Fisika Kayu Mindi (Melia azedarach Linn) dari Hutan Rakyat di Yogyakarta - Harry Praptoyo (Fakultas Kehutanan Universitas Gadjah Mada, 2010)
Anatomical and Physical Properties of Mindi Wood (Melia azedarach Linn) from Community Forest in YogyakartaInformation about mindi wood characteristics is very limited while utilisation of this wood on our society is very extensive. Better knowledge on anatomical and physical wood properties of mindi wood optimizes its utilization. Therefore, this study aims to identify anatomical (macroscopic and microscopic) and physical (moisture content, specific gravity and dimensional changes) wood properties of mindi taken from community forests around Yogyakarta. The macroscopic structural characteristics results showed that annual ring appeared clearly at transversal surface, having single vessel, vasicentric and diffuse parenchyma, rough texture, straight fiber direction, and no resin canal. Cell proportion of wood showed that fibers occupy more than 44%, followed by vessel (20%), parenchyma (19%) and rays (15%). Wood fiber dimension showed fiber length of 0.83 mm, fiber diameter of 14.57µ, and cell wall thickness of 2.50µ. Physical wood properties showed that mindi has 31% moisture content and 0.416 of basic specific gravity. Wood shrinkage from green to kilndry on longitudinal was 3.94 %, tangensial 5.74 %, and radial 2.60 %, with T/R ratio 2.38. Based on T/R ratio value, mindi wood is not recommended for wood construction due to its low dimensional stability. Furthermore, mindi wood also has high longitudinal wood shrinkage and low specific gravity indicating juvenility.